Use of novel thermobrachytherapy seeds for realistic prostate seed implant treatments. Issue 11 (19th October 2016) - Warrell, Gregory; Shvydka, Diana; Parsai, E. Ishmael
Abstract : Purpose: A practical means of delivering both therapeutic radiation and hyperthermia to a deep‐seated target has been identified in the literature as highly desirable, provided it is capable of generating sufficient temperatures over the defined target volume. The authors present continued development of a dual‐modality thermobrachytherapy (TB) seed, investigating its capabilities in delivering prescribed hyperthermia to realistic deep‐seated targets. Methods: The TB seed is based on the ubiquitous low dose‐rate (LDR) brachytherapy permanent implant. Heat is generated by incorporating a ferromagnetic core within the seed and placing the patient in an oscillating external magnetic field, producing eddy currents within the core and hence Joule heating. A strategically selected Curie temperature results in thermal self‐regulation. The magnetic and thermal properties of the TB seed were studied experimentally by means of seed prototypes placed in a tissue‐mimicking phantom and heated with an industrial induction heater, as well as computationally in the finite element analysis solver COMSOL Multiphysics. Patient‐specific seed distributions derived from LDR permanent prostate implants previously conducted at their institution were modeled in COMSOL to evaluate their ability to adequately cover a defined target volume and to overcome the loss of heat due to blood perfusion within tissue. The calculated temperature distributions were analyzed by generating temperature‐volume histograms, which were used to quantify coverage and temperature homogeneity for varied blood perfusion rates, seed Curie temperatures, and thermal power production rates. Use of additional hyperthermia‐only (HT‐only) seeds in unused spots within the implantation needles was investigated, as was an increase in these seeds' core size to increase their power. The impact of the interseed attenuation and scatter (ISA) effect on radiation dose distributions of this seed was also quantified by Monte Carlo studies in the software package Monte Carlo N‐Particle Version 5. Results: Increasing the power production of the seeds, as well as increasing their Curie point, would increase the maximum blood perfusion rate that a given seed distribution could overcome to obtain an acceptable temperature distribution. However, this would also increase the maximum temperatures generated at the seed surfaces. Auxiliary HT‐only seeds serve to improve the temperature uniformity within the target, as well as decrease the seed power generation requirements. Both an increase in their core size and an increase in both seed types' Curie temperatures enhance the resulting temperature coverage. The interseed and scatter effect caused by both the TB and HT‐only seeds was found to reduce the dose to 90% of the target volume ( D 90) by a factor of 1.10 ± 0.02. Conclusions: A systematic approach of combining LDR prostate brachytherapy with hyperthermia is described, and its ability to provide sufficient and uniform temperature distributions in realistic patient‐specific implants evaluated. A combination of TB and HT‐only seeds may be used to produce a uniform temperature distribution in a defined target. Various modeled changes to their design, such as optimization of their Curie temperature, improve their ability to overcome the thermal effects of blood perfusion. The enhanced ISA of the TB and HT‐only seeds must be taken into account for dose calculations, but is manageable.